Targeted pricing, consumer myopia and investment in customer-tracking technology - Irina Baye; Geza Sapi (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2014)
We analyze how consumer myopia influences investment incentives into a technology that enables firms to track consumers' purchases and make targeted offers based on their preferences. In a two-period Hotelling setup firms may invest in customer-tracking technology. If a firm acquires the technology, it can practice first-degree price discrimination among consumers that bought from it in the first period. We distinguish between the cases of all consumers being myopic and when they are sophisticated. In equilibrium firms collect customer data only when consumers are myopic. In that case two asymmetric equilibria emerge, with either one firm investing in customer-tracking technology. We derive several surprising results for consumer policy: First, contrary to conventional wisdom, firms are better-off when consumers are sophisticated. Second, consumers may be better-off being myopic than sophisticated, provided they are sufficiently patient (the discount factor is high enough). Third, in the latter case there is a tension between consumer and social welfare, and correspondingly between consumer and other policies: With myopic consumers, banning customer-tracking would increase social welfare, but may reduce consumer surplus.
Keywords: D43; L13; L15; O30; 330; Price Discrimination; Customer Data; Consumer Myopia